The Eternal Return. Apocatastasis and its Manifestations in Ancient Philosophies: Pythagoreanism, Stoicism, Zoroastrianism, Platonism and Gnosticism - Alexandru LAZĂR (Eon)
This study explores the acceptances of the concept of apocatastasis in five of the most influential philosophical and religious traditions of antiquity: Pythagoreanism, Stoicism, Platonism, Gnosticism and Zoroastrianism. Apocatastasis, defined as 'restoration' or 'return to the original state', was interpreted differently in each of these systems of thought, reflecting distinct views on the nature of the cosmos, time and human destiny. In Pythagoreanism and Stoicism, apocatastasis is closely linked to cosmological cyclicity, implying the periodic renewal of the universe. Platonism emphasizes the restoration of the harmony of the soul and the cosmic order, seen as a return to the perfection of the world’s ideas. In Gnosticism, apocatastasis takes on an eschatological and soteriological dimension, referring to the liberation of the soul from the material world and the return to the divine origin. Zoroastrianism offers a dualistic interpretation, where the final restoration of the world is associated with the triumph of good over evil and the restoration of cosmic order. Through a comparative analysis of these traditions, the study highlights the diversity of the meanings of apocatastasis and its relevance in understanding different visions of universal restoration and salvation.